First record of the mottled spinefoot Siganus fuscescens (Houttuyn, 1782) in Mediterranean waters: a Facebook based detection - AZZURO, ERNESTO; TIRALONGO, FRANCESCO (Mediterranean Marine Science, 2020)
The occurrence of Siganus fuscescens was recorded on March 1st 2020, within the harbour of Gioia Tauro, southern Tyrrhenian Sea (38.44428 N, 15.90459 E). The capture was realized by a recreational fisher and shared through a Facebook group. Here we illustrate this new record and discussed its relevance for Mediterranean bioinvasion research.